Prevalence of Coronary Artery Disease in Rural Areas of Peshawar - Hassan, Mahmood ul; Awan, Zahid Aslam; Gul, Adnan Mahmood; Sahibzada, Waheed A.; Hafizullah, Muhammad (Journal of Postgraduate Medical Institute, 2011)
To see the prevalence of coronary artery disease in rural areas of Peshawar above the age of 30 years. They were interviewed according to performa by trained interviewer. Fasting blood was taken for sugar and serum cholesterol. ECG was done of every subject. height, weight, BMI and blood pressure were recorded. Diagnosis of CAD was made both on the rose questionnaire and ECG criteria according to the minnesota code. The most prevalent risk factors for CAD in rural area in Peshawar were physical inactivity, obesity, hypertention and diabetes mellitus. Coronary artery disease risk factors, i.e. iage > 40 years, hypertension, diabetes mellitus, hypercholesterolemia and physical inactivity were significantly associated with CAD in rural population. CAD was more prevalent in females as comapred to males, through not statistically significant. Male gender, smoking and increase body mass index did not turn out to be important risk factors for CAD in rural area in our study.